Large Voltage Generation of Flexible Thermoelectric Nanocrystal Thin Films by Finger Contact. Issue 21 (18th July 2017) - Choi, Jinyong; Cho, Kyoungah; Yun, Junggwon; Park, Yoonbeom; Yang, Seunggen; Kim, Sangsig
Abstract: This paper demonstrates that thermal energy radiated from a human finger can be converted efficiently into electricity by a nanocrystal (NC) thin film that substantially suppresses thermal conduction, but still allows electric conduction. The converting efficiencies of the chalcogenide NC thin films with dimensions 40 µm × 20 µm × 20 nm, prepared on flexible substrates by a solution process, are maximized by adjusting the NC size. A Seebeck coefficient of S = 1829 µV K −1, and a dimensionless thermoelectric figure‐of‐merit, ZT = 0.68 are achieved at ambient temperature for p‐ and n‐type NC thin films, respectively. A thermoelectric array consisting of p‐ and n‐type NC thin films generates a voltage of 645 mV for a temperature gradient of 10 K. Furthermore, the donut‐shaped pn array can generate a voltage of 170 mV from the heat supplied by an individual's finger. Abstract : For solution‐processable chalcogenide nanocrystal thin films, a Seebeck coefficient of 1829 µV K −1 and a dimensionless thermoelectric figure‐of‐merit of 0.68 are achieved at ambient temperature. The thermoelectric 20 pn pair array generates a voltage of 170 mV from the temperature difference between an individual's finger and the platform's environment.